NETRALITAS WTO DALAM MENYELESAIKAN SENGKETA PERDAGANGAN ANTARA BRASIL VS AMERIKA SERIKAT - Setya Pradhana, Lalu Zidan Pandu; Prakoso, Havidz Ageng (Universitas Jenderal Ahmad Yani, 2025)
Trade dispute cases between Brazil and the United States cover a wide range of issues, from agricultural subsidies to trade policy. However, the neutrality of the WTO in these cases is an aspect that stands out. The WTO strives not to favor any particular country, but rather adheres to the principles of objectivity and fairness. In resolving the dispute between Brazil and the United States, the WTO uses various mechanisms. One of them is the Dispute Settlement Body (DSB), which acts as a forum to resolve disputes between member countries. This process involves stages such as consultations, panels, and appellate bodies. Through this process, the WTO ensures that arguments and evidence from both sides are carefully considered before making a decision. The neutrality of the WTO is reflected in the decisions taken in these cases. While there may be political pressure from member countries, the WTO tries to be unaffected and decide based on the facts and applicable law. This is a very important principle in maintaining the integrity of the international trading system.